EFFECT OF COOKING METHODS AND RICE VARIETY ON THE SENSORY QUALITY AND CONSUMER ACCEPTANCE - Annis Catur Adi; Mahmud Aditya Rifqi; Merryana Adriani; Farapti Farapti; Nila Reswari Haryana; Junaida Astina (Media Gizi Indonesia, 2020)
Rice is the staple food of Indonesian which has superior taste which made it rooted in the eating culture in Indonesia. Nowadays, there is still limited research comparing cooking methods in various rice varieties. This study aim to analyze the eff ect of various cooking methods and rice variety on sensory quality. There were two cooking methods tested, traditional method that combines boiling and steaming, and rice cooker steaming method. Sensory test (quality characteristic) and acceptance test were measured using hedonic scale on 30 semi-trained panelist to evaluate the eff ect of cooking method on four rice variety, that are white rice Berlian Sae, white rice Super Slyp, brown rice, and black rice. Statistical test used was ANOVA and continued with Duncan test. Results showed diff erences in ratio of water and cooking time of various types of rice with diff erent methods. White rice (Slyp Super) with conventional cooking methods was more acceptable to panelist with the characteristics of bright colors, smell, neutral taste, and delicate texture. There was a signifi cant diff erence in panelist acceptance based on type of rice (p<0.05) which brown rice and black rice had lower acceptability than white rice. There was no signifi cant diff erence in acceptance by cooking method (p>0.05), but there was a tendency that traditional method has higher acceptability. Color indicator became main indicator for panelist determined overall acceptability, so that it can be considered in the development of rice cooking methods.